Analisa Sistem Informasi Akuntansi untuk Transaksi Penjualan Laba Rugi dengan Menggunakan VB.Net - Aggy Pramana Gusman; Mardison; Wirda Jihadita Azmi (Universitas Putra Indonesia YPTK Padang, 2019)
Nadya Saiyo cake shop is a business engaged in the sale of various types of cakes. Data processing of sales transactions that are carried out is still manual, this causes delays in delivering sales reports to business owners and inaccurate financial statements of sales transactions. Management of sales transaction data is very important in business activities so that it requires an accounting system that can perform data management functions effectively and efficiently. This study describes the analysis of accounting information systems for computerized profit and loss sales transactions. Which aims to overcome various kinds of problems that exist in Nadya Saiyo cake shop. The establishment of an accounting information system is expected to produce a good information system, with a more efficient working mechanism with shorter time can be generated financial data reports needed, so as to improve the performance of the store and can reduce errors in processing financial data sales transactions